1993
DOI: 10.1007/bf02098580
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of whole blood and urine monoamines in autism

Abstract: Levels of serotonin (5-HT), dopamine (DA), norepinephrine (NE) and epinephrine (E) were determined in the whole blood and urine of 23 children with autism and compared to those of normal children. Very significant group effects (low whole blood 5-HT, high urinary 5-HT and high NE+E in autism) and age effects (urinary 5-HT and DA decrease with age) were found. Moreover, the urinary DA and the whole blood E levels were correlated with clinical findings. The results suggest a maturation defect of noradrenergic sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…However, Gevi et al (2016) found that 5HT concentrations were significantly lower in urine samples from 30 children with ASD compared with 30 matched controls. Thus, our finding that ASD children have elevated urinary 5HT levels is consistent with the results of Hérault et al (1993).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, Gevi et al (2016) found that 5HT concentrations were significantly lower in urine samples from 30 children with ASD compared with 30 matched controls. Thus, our finding that ASD children have elevated urinary 5HT levels is consistent with the results of Hérault et al (1993).…”
Section: Discussionsupporting
confidence: 89%
“…However, whether urinary 5HT levels could be used as an ASD biomarker is a controversial topic. Hérault et al (1993) examined monoamine concentrations in urine samples from 23 children with ASD and 59 matched TD children, and they detected higher 5HT levels in the ASD group. However, Gevi et al (2016) found that 5HT concentrations were significantly lower in urine samples from 30 children with ASD compared with 30 matched controls.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperserotonemia is also associated with restricted and repetitive patterns of behaviors (motor or verbal stereotypies) and interests [24,72,82]. Furthermore, Sacco et al [82] noted a negative correlation between 5-HT levels and neurodevelopmental delay and a positive correlation with stereotyped behaviors; however, the developmental quotient was not correlated with the levels of 5-HT in Hérault et al [114]. In Chugani et al [69], subjects with normal 5-HT levels had a greater chance of improving in "restricted and repetitive behaviors" ADOS scores than those with hyperserotonemia.…”
Section: Asd Core Symptoms and Neurocognitive Outcomesmentioning
confidence: 95%
“…Many studies (Young et al 1978;Garnier et al 1986;Launay et al 1987;Minderaa et al 1987;Barthelemy et al 1988;Garreau et al 1988;Barthelemy et al 1989;Minderaa et al 1989;Martineau et al 1991;Martineau et al 1992;Herault et al 1993;Martineau et al 1994;Minderaa et al 1994;Herault et al 1996;Croonenberghs et al 2000;Mulder et al 2009) have focused on neurotransmitter abnormalities in individuals with autism. Abnormalities in various neurotransmitters have been implicated in the development of autism, including serotonin (5-hydroxytryptamine, 5-HT), dopamine (DA), noradrenaline (NA), gamma-aminobutryic acid, glutamate and neuropeptides.…”
Section: Normalise Neurotransmitters and Neurotransmitter Metabolitesmentioning
confidence: 99%
“…A range of neurochemical studies have attempted to examine excretion of urinary NA and / or adrenaline (A) in individuals with autism compared with controls and have yielded inconsistent findings. Three studies found higher levels of NA and/or A in autism compared to controls Herault et al 1993;Martineau et al 1994), while four studies found no differences (Launay et al 1987;Martineau et al 1992;Minderaa et al 1994;Croonenberghs et al 2000). Therefore as outlined in Table 2, the range of neurotransmitter abnormalities that have been shown to occur in autism provide a rationale for the use of CAM products that are claim to normalise neurotransmitter levels and function such as: high dose pyridoxine and magnesium, metabolites and co-factors of the transmethylation and trans-sulphuration cycles (see Figure 1), vitamin C, zinc and secretin.…”
Section: Noradrenalinementioning
confidence: 99%